Aspects of solid waste management : Bangladesh context - Hoq, Mofizul; Lechner, H. Mrs. (German Cultural Centre, 1994)
Papers presented at an International Workshop on Waste Management in Asian Cities held on April 8-11, 1993 under the sponsorship of German Cultural Centre.